Extremism and Islamophobia Against the Muslim Minority in Sri Lanka (American Journal of Islam and Society, 2023)
Sri Lanka has witnessed many examples of anti-Muslim sentiment and violence since the end of the civil war, especially in 2014 when ethnic unrest affected many. Sinhalese monks and Buddhists appear to have played an important role in the unrest. The long war and ethnonationalist ideology have resulted in a political-religious shift associated with “Buddhist extremism,” which has an association with rioting and aggression against Muslims. The purpose of this study is to investigate how the attitude of Buddhist extremists in Sri Lanka towards Muslim minorities varies from time to time. This study uses the “library research” method where the main data includes books, journals, articles, and references related to research. Sri Lankan Islamophobia and anti-Muslim sentiment is manifested in several dimensions: such as campaigns against halal labels on food, Muslim women’s clothing, the slaughter of livestock in Muslim religious rituals, attacks on mosques and Muslim-owned businesses, mandatory cremation for all Sri Lankans regardless of the religion during the Covid-19 pandemic, and the closure of Islamic schools. Consequently, the government at the very least needs to enforce law and order in a fair and balanced manner for all citizens and ensure policies of multiculturalism and tolerance between religious communities are maintained.